The Influence of the Human Development Index and Gini Ratio on the Poverty Level in West Java Province - Fibriani, Mega; Huda, Nurul (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to